Frequency reconfigurable antenna array using defected ground structure for outdoor wireless communication systems / M. A. Aris ...[et al.] - Aris, M. A.; Ali, M. T.; Abd Rahman, N. H.; Pasya, I. (UiTM Press, 2016)
-This paper proposes frequency reconfigurable antenna for outdoor wireless communication systems, the 4 x 4 array antenna has designed at two resonant frequencies 7.5 GHz and 8.85 GHz. The periodic dumbbell geometry etched on the ground layer newly proposed with dual functionality, to control desired frequency and to couple radiating patches at the top substrate with feeding line at the bottom substrate. The reconfigurability of the patch antenna is controlled by utilizing the copper pad of the feeding network with OPEN and SHORT states. The reconfigurable antenna has been simulated and optimized using Computer Simulation Technology (CST) to get the desired responds. The good agreement between simulation and measured results indicates that the frequency reconfigurable patch array antenna using Periodic Dumbbell Slotted Aperture Structure (FRPDSA) is feasible to support outdoor wireless communication systems.